(In press) Psychological Support Factors for Caregivers of Children with Disabilities: A Literature Review - Hardiani, Alifa Fauziah; Wiwin, Hendriani (Indonesian Journal of Disability Studies, 2026)
This research aims to explore contributing factors to the psychological support of caregivers of children with disabilities through a traditional literature review approach based on studies conducted over the last decade and published in reputable journals. The analysis emphasizes caregiver empowerment, adaptive coping strategies, and social support in navigating caregiving challenges, enhancing caregiver well-being and resilience. Findings underscore the importance of parental involvement in interventions for improving children's well-being and highlight the significance of family adaptation and resilience in coping with challenges. Future research should focus on innovative interventions to enhance caregiver empowerment and emotional regulation, while sustainable support networks and resources are essential for long-term caregiver support. Collaboration among healthcare professionals, policymakers, and community organizations is crucial for effective implementation and evaluation of interventions, fostering optimal development and well-being for both caregivers and children with disabilities.